SOME OBSERVATIONS ON FISHES AND THEIR PARASITES OF DARBANDIKHAN LAKE, KURDISTAN REGION IN NORTH IRAQ - Abdullah, Younis S.; Abdullah, Shamall M. A. (European Scientific Journal, ESJ, 2015)
A total of 255 freshwater fishes, belonging to 17 species, namely: Barbus barbulus, B. grypus, Capoeta trutta, Capoeta umbla, Carasobarbus luteus, Carassius auratus, Chondrostoma regium, Cyprinion macrostomum, Cyprinus carpio, Garra rufa, Hemiculter leucisculus, Hypophthalmichthys molitrix, Luciobarbus esocinus, Squalius lepidus (Family Cyprinidae), Mystus pelusius (Bagridae), Silurus triostegus (Siluridae) and Mastacembelus mastacembelus (Mastacembelidae), were collected from Darbandikhan Lake, southeast of Sulaimani city, Kurdistan region, Iraq, from March 2012 to the end of October 2012. The fishes were examined for ectoparasites and endoparasites. The study revealed the existence of 45 species of parasites including: seven species of protozoans, 29 species of monogeneans, two species of trematodes, one species each of cestode and nematode, two species of acanthocephalans and three species of crustaceans. The present study revealed that Dactylogyrus suchengtaii and D. carassobarbi were the most parasites prevalent (100% and 90.90%, respectively) in the lake, while Scyphidia arctica was scarce (1.44%). The fish C. trutta was highly infected with parasites (nine species), followed by S. lepidus (eight species) and both C. luteus and M. mastacembelus (six species each), while G. rufa and H. molitrix were less infected (one species each). The ciliated protozoan Ichthyophthirius multifiliis was recorded on seven species of fishes with prevalence ranged between 2.89% and 23.52%, followed by the crustacean Lernaea cyprinacea which was recorded on four species of fishes (5% - 27.27%).